Analisis proyeksi pertumbuhan penduduk dan volume sampah DKI Jakarta terhadap dampak yang ditimbulkan - Diani, Meutia Rin; Haniifah, Diinii; Dianty, Fatima Risha (Journal of Waste and Sustainable Consumption, 2024)
Background: In forthcoming years, the accumulation of waste in DKI Jakarta is anticipated to escalate. This escalation is primarily attributed to population expansion, alterations in consumption patterns, and inadequate waste management practices. To foster public awareness regarding the burgeoning waste volume in Jakarta, it becomes imperative to provide projections of population and waste growth for the ensuing years. This enables individuals to gain a better comprehension of the detrimental environmental, social, and economic repercussions associated with escalating waste levels and allows for proactive measures to be undertaken. Methods: The research methodology employed in this study comprises a literature review and case study analysis, utilizing a descriptive analytical approach. The research commenced with the retrieval of population data for Jakarta spanning the period from 2017 to 2019, alongside waste volume data collected between 2015 and 2017. Subsequently, this data was utilized to analyze the projected growth and volume of waste generation from 2020 to 2029. Data sources encompassed scientific articles, journals, regulatory documents, and local government annual reports. Three distinct methods were employed in projecting population and waste volume, namely arithmetic, geometric, and exponential methods. Findings: The prognostic outcomes for the total population of DKI Jakarta in 2029, as per arithmetic, geometric, and exponential calculations, are estimated at 12,042,000; 12,170,580; and 12,183,378 individuals, respectively. Concurrently, waste generation volume for the same year is anticipated to reach 8,316.49; 8,405.29; and 8,414.13 cubic meter per day. Conclusion: It is anticipated that the population and waste volume of DKI Jakarta will persistently surge over the ensuing decade. In the absence of effective waste management practices, adverse ramifications such as a air pollution, water contamination, soil degradation, compromised sanitation standards, public health hazards, heightened potential for the social discord, tarnished tourism reputation, and escalated waste processing expenditures are likely to ensue. Nevertheless, these challenges can be mitigated through the implementation of urban waste management protocols in alignment with established procedures and concerted efforts among stakeholders to achieve optimal waste management outcomes.